Die kinematischen Unterschiede zwischen akkuratem und ungenauem Squash-Vorhandspiel bei Athleten verschiedener Leistungsklassen - Williams, B. K.; Sanders, R. H.; Ryu, J. H.; Graham-Smith, P.; Sinclair, P. J. (Journal of Sports Sciences, 2020)
To maintain the accuracy of squash shots under varying conditions, such as the oncoming ball`s velocity and trajectory, players must adjust their technique. Although differences in technique between skilled and less-skilled players have been studied, it is not yet understood how players vary their technique in a functional manner to maintain accuracy under varying conditions. This study compared 3-dimensional joint and racket kinematics and their variability between accurate and inaccurate squash forehand drives of 9 highly skilled and 9 less-skilled male athletes. During inaccurate shots, less-skilled players hit the ball with a more open racket, demonstrating a difference in this task-relevant parameter. No joint kinematic differences were found for accuracy for either group. Coordinated joint rotations at the elbow and wrist both displayed a "zeroing-in" effect, whereby movement variability was reduced from the initiation of propulsive joint rotation to a higher consistency at ball-impact; potentially highlighting the "functionality" of the variability prior to the impact that enabled consistent task-relevant parameters (racket orientation and velocity) under varying conditions. Further, highly skilled players demonstrated greater consistency of task-relevant parameters at impact than less-skilled players. These findings highlight the superior ability of highly skilled players to adjust their technique to achieve consistent task-relevant parameters and a successful shot.